Balancing Economic Growth and Cultural Preservation: Navigating the Challenges of Globalization in Nepal - Neupane, Bibek Kanta; Neupane, Madhab Prasad; Tamang, Bidhyan (NPRC Journal of Multidisciplinary Research, 2025)
Background: Globalization has significantly influenced political and economic domains worldwide, including Nepal. While it has presented opportunities for economic growth and international integration, it has also raised concerns about inequality, cultural homogenization, and policy dependence. Understanding globalization's theoretical underpinnings and contextualizing its impacts on Nepal can provide a comprehensive perspective on its dual-edged nature.Objective: The objective of this study is to examine the interplay between globalization and Nepal, exploring its theoretical perspectives, economic liberalization journey, positive impacts, and the challenges it poses. The research also seeks to identify pathways for Nepal to leverage globalization while mitigating its adverse effects.Methods: This study employs a qualitative approach, synthesizing data from policy documents, economic reports, and scholarly literature. Theoretical frameworks of globalization—including neoliberalism, reformism, progressive radicalism, and traditionalism—are used to analyze Nepal's experience with globalization. Case studies and sectoral data are incorporated to support arguments.Findings: Globalization has contributed to Nepal's economic diversification, increased foreign investments, and export market expansion. However, it has also exacerbated issues such as income inequality, labor migration, cultural erosion, and economic dependence. Gendered impacts remain underexplored, and multinational corporations (MNCs) have often undermined local industries. Multilateral organizations and global power dynamics further shape Nepal's vulnerabilities and opportunities.Conclusion: While globalization has brought economic and social benefits to Nepal, it also perpetuates structural inequalities and cultural challenges. Emphasizing equitable policies, sustainable practices, and strategic reforms can help Nepal navigate globalization's complexities. Preservation of cultural diversity and enhancing policy autonomy are essential for fostering resilience in an interconnected world.Novelty: This study uniquely combines theoretical perspectives on globalization with Nepal's specific economic and social context, offering a balanced analysis of its multifaceted impacts. It highlights the gendered dimensions and the role of multilateral organizations, providing actionable insights for policy reforms tailored to Nepal’s unique challenges and strengths.